Penerapan Jaringan Fiber Optik untuk Meningkatkan Keamanan dan Stabilitas Layanan RT/RW Net Berbasis Pemberdayaan Pemuda - Jafaruddin Gusti Amri Ginting; Dadiek Pranindito; Yosita Dwiani Suryaningtiyas; Zein Hanni Pradana (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Limited internet service quality remains a major challenge in community-based RT/RW Net networks that rely on copper cables, mainly due to their vulnerability to lightning strikes and technical disturbances. This condition affects educational activities, religious services, and community-based economic activities, including home-based micro-enterprises and digital religious outreach. This community service program aims to modernize network infrastructure through the implementation of fiber optic technology that provides higher stability, safety, and sustainability, while strengthening local capacity in network management through technical and managerial training for youth groups. The implementation stages include coordination with community partners, deployment of fiber optic networks, network planning simulation using OptiSystem to ensure optical attenuation remains within safe limits, training on RT/RW Net management supported by cloud-based documentation systems, and hands-on training on fiber optic installation and MikroTik router configuration. The results show that the fiber optic network has been successfully implemented and currently serves 11 households and one mosque that regularly utilizes internet access for weekly live-streamed religious lectures. From a technical perspective, the fiber optic infrastructure improves network stability and reduces the risk of equipment damage caused by lightning. From social and economic perspective, reliable internet access supports distance learning, digital religious activities, and the operation of home-based micro-enterprises. The active involvement of local youth in installation and training activities enhances local technical capacity and contributes to the sustainability of the RT/RW Net system. This program demonstrates that fiber optic deployment combined with community empowerment can serve as an effective model for community-based digital infrastructure development.